International Legal Preconditions for Development of Student Forestries as a Form of Education for Sustainable Development of Forest Resources - Anzhela Slepchenko (Vasyl Stefanyk Precarpathian National University, 2018)
The conscious need for sustainable development of forest resources and the reflection of this idea in international law give increased attention to forestry education and training. Student forestry is one of the legal forms of extracurricular education in the environmental and naturalistic direction in Ukraine. Its primary task is a provision of knowledge, skills and competences in the field of forestry and enhancing environmental culture among children and young people. The availability of sound international legal preconditions for strengthening all forms of forestry education, analyzed by the author, should motivate legal scholars to focus their attention on the legal problems of development of school forestry in Ukraine.